F13 Deviant language patterns in huntington's spontaneous speech. (13th September 2016) - Hinzen, Wolfram; Morey, Cati; Rossello, Joana; Salvador, Raymon; Garcia-Gorro, Clara; Camara, Estela; Diego-Balaguer, Ruth de
Abstract : Background: Language has been shown to be affected in Huntington's disease (HD) in several experimental tasks, independently of cognitive disabilities and since the earliest stages of the disease. However, studies of spontaneous speech are scarce and provide contradictory results. Aims: To systematically profile the earliest spontaneous speech errors in HD and to test whether they extend to referential dysfunction in production, as it has been described in previous experimental work testing comprehension. Methods: 28 native HD gene-carriers (9 pre-HD) and 28 matched controls were recorded while telling the Cinderella story using a visual support. Speech samples were transcribed and rated by two independent raters using Computarised Language Analysis (CLAN). Measures were normalised and errors were clustered in five different components. All participants underwent MRI scanning and high resolution T1 images were analysed using voxed-based morphometry (VBM) in order to study brain atrophy. Results: Manifest HD patients showed increased errors in all five components: Quantitative, comprising the Mean Length of Utterances, the Number of Words, and Words per Minute; Fluency, capturing disturbances in the flow of speech due to abnormal Pauses and Truncations; Connectivity, related to the combining of clauses; Reference, capturing all variables relating to the referential use of language in discourse such as the use of noun phrases to identify objects and establish topics of the discourse; Concordance, related to deficits in grammatical Agreement. In the case of the preHD group, these differences were observed in Connectivity and Reference measures. Correlations of these measures with the voxels showing VBM differences between patients and controls showed that the Quantitative measure correlated with atrophy in bilateral caudate and putamen. The remaining components showed no significant correlation with the VBM differences. Conclusions: Striatal atrophy is associated to spontaneous speech deficits. However, deficits in spontaneous speech in HD are characterised not only by dysfluencies related to motor dysfunction but also by syntactic and referential errors in their discourse. Specific deficits in connecting clauses and reference are detectable even before overt clinical symptomatology.